Sistem Peringatan Dan Penanganan Dini Kebakaran Berbasis Internet Of Things(IoT) - Aldo Napu; Olivia Kembuan; Kristofel Santa (Program Studi Teknik Informatika, 2022)
Fire is one of the disasters that often occur in Indonesia. Especially in densely populated areas that have the potential to cause problems in the event of a fire. The obstacle that occurs is that firefighters are often late in handling due to various factors, so the damage and losses due to fires are greater. This study aims to create an internet of things (iot) based fire detection system. The system uses 3 sensors, namely the Irflame fire sensor, the Mq-2 gas sensor and the Dht11 temperature sensor and are assembled on the Nodemcu ESP8266 microcontroller. In experiments that have been carried out in a 3.5 mx 3.5 m room, the fire sensor can detect a small fire up to a distance of 30 cm and a large fire of 230 cm, then it will turn on the water pump when a fire is detected. When the Mq-2 sensor detects a gas leak above 300 PPM, it will turn on the fan to decompose the gas. The DHT11 sensor reads the room temperature value continuously and is set to a minimum temperature of 32˚C, the system will give a warning from the buzzer. The result of the design of this tool is that the system can send information through the blynk application on the user's smartphone and can handle fire signs based on the designed output.